Komunikasi Pemasaran PT Dalim Fideta Kornesia dalam Menciptakan Loyalitas Pelanggan - Fitriansyah, Fifit; Alifiah, Lidya; Widiansyah, Apriyanti (LPPM Universitas Bina Sarana Informatika, 2024)
In the manufacturing industry that is currently growing rapidly, PT Dalim Fideta Kornesia must be able to survive and continue to compete in improving the quality of products and services provided so that it can compete with competitors in reaching customers. Companies that produce wigs must continue to try to provide solutions that are requested by customers. Not a few diverse demands make companies have to innovate more in meeting customer needs. This study aims to find out how the marketing communication strategy carried out by PT Dalim Fideta Kornesia in maintaining customer loyalty. In a company, customer loyalty has an important role and is the main goal of a company. Therefore, companies need an effective marketing communication strategy to maintain customer loyalty. This research uses a qualitative approach with a descriptive method. Data analysis is carried out using triangulation techniques to confirm the results of in-depth interviews related to findings or phenomena that occur in the field. The results of this study reveal that marketing communication in creating customer loyalty are carried out by maintaining product quality and improving customer service to customers regarding complaints, criticisms, and suggestions as well as providing solutions and meeting customer needs and desires for products. The demand for the use of technology is also a concern for the Marketing Division to design and process messages through various media, especially social media